Pengaruh Sectio Caesarea Metode Eracs Terhadap Percepatan Mobilisasi pada Ibu Bersalin di RS Hermina Daan Mogot Tahun 2022 - Warmiyati, Warmiyati; Ratnasari, Febi (Cerdika: Jurnal Ilmiah Indonesia, 2022)
The problem that often arises in post sectio caesarea (SC) patients is the fear of early mobilization due to pain. Approximately 60% of patients have very severe pain, 25% moderate pain and 15% mild pain. SC ERACS method is claimed to reduce postoperative pain, and allow a faster recovery process. The purpose of this study was to determine the effect of SC ERACS method on the acceleration of mobilization in women giving birth. The research method used is a quasi-experimental design with a nonequivalent pretest-posttest control group design. The results of univariate analysis showed that the mean of mobilization in conventional SC was 20.41 hours after surgery, and in ERACS SC it was 10 hours after surgery. The results of the bivariate analysis showed that there was an effect of the ERACS method on the acceleration of mobilization in postpartum mothers. The conclusion is that there is an effect of SC ERACS method on the acceleration of mobilization in postpartum mothers at Hermina Daan Mogot Hospital in 2022. Suggestions are that the hospital is expected to provide counseling on the implementation of early mobilization before surgery, so that after surgery the patient already has knowledge about early mobilization.